Aflatoxin surveillance in Kenya - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The dataset contains results of a project measuring the prevalence of aflatoxin contamination in maize purchased at retail sites across Kenya in 2021. Samples of packaged flour and informally milled (posho) flour were purchased from a variety of retailers across ten urban sampling sites every two months for a duration of one year. Samples were transported after purchase to the University of Nairobi for laboratory analysis to measure the prevalence of aflatoxin contamination. The results of this analysis are included in this dataset, along with information on the location of the mill where the flour was processed, the sampling location where it was purchased, the timing of data collection and the type of flour.